2018
DOI: 10.3892/or.2018.6485
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits liver cancer by inhibiting DAMP molecule HSP70 and TLR4 signaling

Abstract: Curcumin has been revealed to inhibit liver cancer, however, no studies have reported that the mechanism of curcumin's action on liver cancer is related to damage-associated molecular pattern (DAMP) molecules heat shock protein 70 (HSP70) and the toll-like receptor 4 (TLR4) signaling. This study aimed to investigate whether the activation of TLR4 signaling by HSP70 could be inhibited by curcumin, thus investigating the possible mechanism of curcumin in the inhibition of liver cancer. Western blotting was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Curcumin administration can reduce activation of microglia/macrophages and neuronal apoptosis through a mechanism involving the TLR4/MyD88/NF-κB signaling in experimental traumatic brain injury [ 70 ]. Recently, a study has shown that curcumin inhibits DAMP molecule HSP70 and TLR4 signaling in liver cancer cells [ 72 ].…”
Section: Bioactive Phytochemicals Targeting Tlr4 and Oxidative Strmentioning
confidence: 99%
“…Curcumin administration can reduce activation of microglia/macrophages and neuronal apoptosis through a mechanism involving the TLR4/MyD88/NF-κB signaling in experimental traumatic brain injury [ 70 ]. Recently, a study has shown that curcumin inhibits DAMP molecule HSP70 and TLR4 signaling in liver cancer cells [ 72 ].…”
Section: Bioactive Phytochemicals Targeting Tlr4 and Oxidative Strmentioning
confidence: 99%
“…Finally, we disclosed that curcumin, an active component of turmeric, displays various pharmacological activities [32]. The promising role of curcumin against different diseases is widely publicized [33].…”
Section: Discussionmentioning
confidence: 99%
“…And activation of TLR4 would trigger inflammatory and catabolic responses by chondrocytes, thus is closely involved in OA-related cartilage damage 13 . The main aim of our study was to determine whether the TLR4 inhibitory activity of curcumin, which has been demonstrated in other pathological conditions such as liver cancer 15 , traumatic brain injury 16 and atherosclerosis 17 , contributed to its protective anti-inflammatory effect of curcumin on OA. And LPS, a canonical TLR4 activator, was used as a tool to up-regulate TLR4 in the joints.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, the TLR4 inhibitory activity of curcumin has been demonstrated in liver cancer HepG2 cells 15 , experimental traumatic brain injury 16 , and apolipoprotein E-knockout mice 17 etc. , which has been believed as a key underlying mechanism of curcumin’s anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%